Agaricus radiatosquamulosus sp. nov. of A. subg. Spissicaules from Pakistan - Bashir, Hira; Fatima, Nadia; Izhar, Aiman; Niazi, Abdul Rehman; Khalid, Abdul Nasir; Callac, Philippe (Phytotaxa, 2023)
In recent studies, new species and sections were described in Agaricus subg. Spissicaules. We intended to update this subgenus by including all these recent taxa, some interesting sequences retrieved in GenBank, and two new collections from the Punjab Province, Pakistan. Both morphological and phylogenetic approaches were used. Maximum Likelihood tree based on rDNA ITS sequences revealed that the sequences of the new specimens from Pakistan form a clade with five sequences from India retrieved from GenBank. For the seven samples of this clade, we described the new species Agaricus radiatosquamulosus based on the morphology of the two collections from Pakistan. This new species, which belongs to the recently proposed A. sect. Fulventes was compared to the three other species of this section. Except for the small-sized A. nanofulvus, the other species are difficult to recognize without DNA sequence data. The four species differ from each other at a poly T in ITS2. In addition, each of them is distributed on different continents. Agaricus radiatosquamulosus is the first report of a species of A. subg. Spissicaules in Pakistan. In addition, a sequence from GenBank identified as A. lanatoniger matches with another sample from New Zealand in A. sect. subrutilescentes. In absence of formally published taxonomic treatment, we provisionally named these samples A. cf. lanatoniger.